Identifikasi Spesies Stafilokokus Pada Ikan Kerapu Di Kabupaten Karangasem Dengan Analisis Sekuen 16S rRNA (SPECIES IDENTIFICATION OF STAPHYLOCOCCUS ON GROUPER IN KARANGASEM REGENCY BASED ON 16S RIBOSOMAL RNA SEQUENCE ANALYSIS) - Besung, I Nengah Kerta; Mellisandy, Ketut Wella; Mahardika, I Gusti Ngurah Kade (Buletin Veteriner Udayana; Vol. 7 No. 1 Pebruari 2015, 2015)
This study aims to identify the species Staphylococcus grouper in Karangasem Regency.Faeces samples were collected and grown on media Blood order and identified by Gram staining.Suspected staphylococcal bacterial culture, included in the 10% Chelex media. The 16S rRNAgene fragments amplified from DNA (deoxyribonucleic acid) by Polymerase Chain Reaction(PCR) with specific primers that is Tsta G422 and Tstag 765. PCR (Polymerase Chain Reaction)products were sequenced in Barkley Sequencing Facility in the USA The result of sequencing wasedit and sorted using MEGA 5.0. Final sequence from each isolate was aligned using database in GenBank by fitur of BLAST. Several of standard sequences were downloaded to construct thefilogenetik tree. Species which can be confimed was Staphylococcus warneriwith homology valueof 100% with the data in GenBank.
Keywords: grauper; Staphyloccocus; PCR; 16S rRNA